Information and Communication Technology (ICT) and International Terrorism: Boko Haram and Al Shabaab in Perspective (International Journal of Scientific Research and Management (IJSRM), 2018)
This study examined the relationship between Information and Communication Technology (ICT) and international terrorism with regards to the activities of terrorist groups. This was premised on the fact that ICT has created a network with a truly global reach for advancement of terrorist activities. The internet technology makes it easy for an individual to communicate with relative ease and anonymity, quickly and effectively across borders to an almost limitless audience. This factor made ICT and their innovative tendencies of the social media like Whatsapp, Facebook, Instagram, Youtube, Twitter etc to serve as veritable tool and motivation for terrorist groups and their activities. Historical and descriptive methods were employed in this study hence data were drawn from relevant primary and secondary sources which included published and unpublished materials. The findings of the study revealed that increased availability of ICT and other innovative tendencies has made it easier for terrorist organizations to communicate, recruit, radicalize as well as mobilize individuals to plan and coordinate terrorist attacks. Based on the above findings, it was recommended among others that understanding terrorist recruitment through the social media was vital to counter-terrorism. Hence, understanding how and why an individual is radicalize and recruited into a terrorist organization is therefore an important part of addressing the fight against terrorism. Accordingly, there should be investment in scientific research and industrial development that are more resistant for terrorist use.